Molds, Mushrooms, and Mycotoxins. - Christensen, Clyde M. (University of Minnesota Press, 1975)
As Professor Christensen has made evident in his earlier books, including The Molds and Man, fungi are significantly interesting in their life-styles and in the many ways in which they affect man. Here he continues his exploration of the lives of the fun.